2019
DOI: 10.1016/j.jss.2018.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Bladder-Drained Pancreas Transplantation: Urothelial Innate Defenses and Urinary Track Infection Susceptibility

Abstract: Conclusions: These in vivo and in vitro data suggest that BD pancreatic exocrine secretions inactivate the bladder innate defenses, which facilitate UPEC growth and underpins the increased susceptibility of patients who underwent BD pancreas transplantation to rUTIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Two recent long‐term studies reported that >40% of patients with bladder drainage require enteric conversion at some point in time 197,207 . Additionally, bladder drainage increased the rate of metabolic and urologic complications, 188,198,208–216 and did not improve immunologic outcome of either SPK 187,190‐192,196‐198,205,206,208,214,217,218 or solitary pancreas transplantations 70,171,219 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent long‐term studies reported that >40% of patients with bladder drainage require enteric conversion at some point in time 197,207 . Additionally, bladder drainage increased the rate of metabolic and urologic complications, 188,198,208–216 and did not improve immunologic outcome of either SPK 187,190‐192,196‐198,205,206,208,214,217,218 or solitary pancreas transplantations 70,171,219 …”
Section: Discussionmentioning
confidence: 99%
“…190 Two recent long-term studies reported that >40% of patients with bladder drainage require enteric conversion at some point in time. 197,207 Additionally, bladder drainage increased the rate of metabolic and urologic complications, 188,198,[208][209][210][211][212][213][214][215][216] and did not improve immunologic outcome of either SPK 187,[190][191][192][196][197][198]205,206,208,214,217,218 or solitary pancreas transplantations. 70,171,219 Duodeno-duodenostomy (vs. duodeno-jejunostomy) was not considered to clearly increase the overall rate of surgical complications after pancreas transplantation, despite higher rates of bleeding.…”
Section: 2%mentioning
confidence: 99%
“…This is in contrast to previous reports, where infectious complications were the main cause of morbidity and mortality after PT and the administration of broad-spectrum prophylactic antibiotics, antifungal, and antiviral agents was recommended [47,48]. These recommendations, however, are based on smaller studies with mainly bladder-drained PT, which involves a higher risk of recurrent infections and urologic complications [7,49]. In our cohort, all PTs were performed with enteric drainage, as enteric complications are rare overall [12,50] and the need for later conversion from bladder to intestinal exocrine drainage is avoided [7].…”
Section: Discussionmentioning
confidence: 86%
“…A single pedicle of donor iliac artery bifurcation (Y‐graft) is then anastomosed to the common iliac artery. Donor duodenum can be anastomosed to recipient's small bowel or bladder to create drainage for exocrine secretions 58,59 . If kidney transplantation is also performed, this is typically placed in left iliac fossa.…”
Section: Transplantation Options For Diabetic Kidney Diseasementioning
confidence: 99%